Une revenance dans l’écriture poétique : les disparus et Vittorio Sereni - Yannick Gouchan (Conserveries Mémorielles)
Vittorio Sereni (1913-1983) is one of the major Italian poets in the twentieth century. His work is marked by an existential injury due to his imprisonment during the Second World War making it impossible for him to take part in History in that period. The sense of guilt and absence affect his writing and especially the definition of remnants in two forms: the return of the dead to the poet and an obsession with the return of the traumatic past event. We will therefore study the encounter between the poet and the dead, showing how the poet can become a remnant too. What sort of remnants do influence poetry? Where do they appear? How is the encounter expressed in the writing?